Metabolic remodelling driven by MYC overexpression regulates the p53 tumour suppressor response - Edwards-Hicks, Joy (The University of Edinburgh, 2018)
The MYC onocogene is frequently overexpressed in human cancer due to its capacity to promote cell growth and cell proliferation. MYC overexpression activates the p53 tumour suppressor pathway, which resists the pro-tumourigeneic program elicited by MYC. How MYC overexpression engages p53 is yet to be elucidated, and in this study I carried out a large metabolic siRNA screen to determine whether p53 responds to a specific MYC-driven metabolic pathway. Two clear lipid metabolic pathways emerged from the siRNA screen: PPARγ/arachidonate metabolism and de novo sphingolipid synthesis. Knockdown or inhibition of PPARγ increased p53 levels, and PPARγ ligands decreased following MYC overexpression. Knockdown of ceramide synthesis depleted p53 levels, and MYC overexpression increased de novo ceramide synthesis. This demonstrated that MYC-driven ceramide synthesis positively regulates p53, and highlights the role of cell metabolism in the tumour suppressor response to MYC deregulation.
Keywords: MYC onocogene; TP53 tumour suppressor pathway; p53; metabolic pathways; MYC deregulation